LITERATURE REVIEW: APPLICATION OF POSITIVE ABILITY EXERCISES TO INCREASE LOW SELF-ESTEEM IN CLIENTS WITH SCHIZOPHRENIA - Ichya' Ulumudin, Safetyan; Aristawati, Evy; Huda, Nurul; Zuhroidah, Ida; Cahyono, Bagus Dwi (Universitas Airlangga, 2022)
Introduction: Positive ability is the ability or positive aspect of an individual to identify the ability that exists in the individual so that clients can choose activities according to their abilities. Patients with low self-esteem see that they are not helpful and feel unable to; by practising positive abilities, they can explore aspects of their positive abilities so that they are expected to see themselves as valuable and become good individuals. Methods: The study used was a literature review of positive ability exercises. Searching for the article is done by Google Scholar or Google Scholar, published from 2015 to 2020, accessed full text in PDF format. Of the five studies used, three used the case study method, one used the Quasi-Experimental Pre-post without control method, and the other used the lecture and discussion method. The search strategy in this literature study uses databases, including Science Direct, Google Scholar and Garuda. Results: A literature review of 7 articles showed that positive ability training varied widely. Conclusions: Positive ability training can overcome nursing problems in patients with schizophrenia with impaired self-concept and low self-esteem.